TYPICAL FORMS OF LIVER PATHOLOGY IN CHILDREN - Peter F. Litvitskiy; Larisa D. Maltseva; Olga L. Morozova ("Paediatrician" Publishers LLC, 2018)
This lecture for the system of postgraduate medical education analyzes causes, types, key links of pathogenesis, and manifestations of the main typical forms of liver pathology - liver failure, hepatic coma, jaundice, cholemia, acholia, cholelithiasis, and their complications in children. To control the retention of the lecture material, case problems and multiple-choice tests are given.